Implementation of Rotary Dryer for Cassava Drying as a Raw Material for Mocaf Flour Production - Sudarmini, Sudarmini; Subrata, Arsyad Cahya; Hakika, Dhias Cahya (Universitas Negeri Semarang, 2023)
Modified cassava flour (mocaf) is one of the innovative cassava processed products with high market value and promising business prospects as a substitute for imported wheat flour. The women's farming group (KWT) Ngudi Sari, located in the village of Tanjungsari, Gunungkidul, has processed cassava into mocaf flour and various cassava-based products, including cassava chips, tiwul, gatot, mocaf sticks, and various cookies. During the production process of mocaf flour, one of the common challenges faced is the drying of cassava chips, which has traditionally relied on sunlight and home-based drying methods. With the increasing demand for mocaf flour, large-scale drying of cassava chips becomes necessary. To address this challenge, a technology of rotary dryer is implemented to KWT Ngudi Sari to enhance the efficiency and effectiveness of the cassava raw material drying process. This outreach project aims to empower KWT Ngudi Sari and boost the production capacity of the resulting mocaf flour. The application of this appropriate technology is expected to improve the quality of cassava as a raw material for mocaf production and enhance its energy efficiency, thus contributing to the economic development of KWT Ngudi Sari. Throughout the project, mentoring, monitoring, and evaluation are also conducted to measure the progress in knowledge and skills of the partners involved.